Analisis Gaya Bahasa dalam Lirik Lagu “Dialog Hati” Nadzira Shafa - Indriani, Windy (Kajian Bahasa dan Sastra (KABASTRA), 2025)
This research analyzes the language style contained in the lyrics of the song Dialog Hati popularized by Nadzira Shafa. This song was chosen because the lyrics are deep and rich in distinctive language styles, which have not been studied much in previous studies. The approach used in this research is a qualitative approach with descriptive analysis techniques to explore the meaning and richness of language styles in the song lyrics. The research data is obtained through the text study method, by identifying and classifying the types of language styles found in the lyrics of the song Dialog Hati. This research refers to Keraf's theory of stylistics which distinguishes stylistics based on its type and function, including rhetorical majas and figurative majas. By using the read-and-record technique, the author analyzes the entire song lyrics and records all the stylistic forms that appear. The results show that in this song there are quite a variety of language styles used to describe feelings and inner conflicts in human relationships. The language style not only enriches the meaning of the lyrics, but also creates a deep emotional atmosphere for the listeners.